Heat Transfer and Fluid Flow in Double Pipe Heat Exchanger, Part II: Numerical Investigation - Kotian, Shreyas; Methekar, Nachiket; Jain, Nishant; Naik, Pritish (Asian Review of Mechanical Engineering, 2020)
Analysis of thermo hydraulic characteristics in a simple configuration of the double-pipe heat exchangers adds a great value to the design of heat exchangers. This paper presents a comparison of the experimental observations and numerical predictions for the thermal characteristics of the double pipe heat exchanger. A CAD design was developed and the Realizable k-ε mathematical model coupled with enhanced wall treatment gave the closest results. Experiments were performed for 60 ≤ Re ≤ 240 for two different inlet temperatures of the hot fluid, 50°C, and 70°C keeping the inlet temperature of the cold fluid constant at 31°C. Temperature gradients extracted from ANSYS Fluent were compared with the experimental data. Further, pressure and temperature contours for the hot and cold streams were generated to analyze the performance parameters.